Trauma Incidence and Care in Tanzania : Report of Trauma Cases in a Sample of Health Facilities with a Focus on Road Traffic Crashes (2019-2020) - World Bank (Washington, DC, 2022)
Injuries due to road traffic crashes (RTCs) are one of the major causes of mortality in developing countries, with higher numbers of fatalities in the Sub-Saharan African (SSA) region and specifically in Tanzania, where fatalities due to RTCs are almost 1.7 times the global rate. This critical problem was at the heart of the Government of Tanzania’s decision to adopt the road safety policy, 2009 with the key aim of reducing mortality and morbidity for crash victims. The outcomes for the crash victims can be improved by strengthening emergency medical services (EMS) and better, reliable trauma data. Yet, survey findings from the report the state of EMS in SSA reveal that very few countries in the SSA region have developed systematic and sustainable EMS systems at scale. The goal of this report is to present some of the insights that can be gained from the one year of detailed trauma data collection across 13 health facilities in Tanzania in order to encourage further use of these data to help inform policymakers on the current situation and help feed into more data-informed decisions.